A 280mV-to-1.1V 256b reconfigurable SIMD vector permutation engine with 2-dimensional shuffle in 22nm CMOS - Hsu, S.; Agarwal, A.; Anders, M.; Mathew, S.; Kaul, H.; Sheikh, F.; Krishnamurthy, R. (2012 IEEE International Solid-State Circuits Conference, 2012)
Energy-efficient SIMD permutation operations are key for maximizing high-performance microprocessor vector datapath utilization in multimedia, graphics, and signal processing workloads [1-3]. A wide SIMD vector permutation engine is required to achieve high-throughput data rearrangement operations on large data sets, with scaled supply voltages to deliver high energy efficiency. An ultra-low-voltage reconfigurable 4-way to 32-way SIMD vector permutation engine consisting of a 32-entry × 256b 3-read/1-write ported register file with a 256b byte-wise any-to-any permute crossbar for 2-dimensional shuffle is fabricated in 22nm CMOS. The register file integrates a vertical shuffle across multiple entries into read/write operations, and includes clockless static reads with shared P/N dual-ended transmission gate (DETG) writes, improving register file V MIN by 250mV across PVT variations with a wide dynamic operating range of 280mV-1.1V. The permute crossbar implements an interleaved folded byte-wise multiplexer layout forming an any-to-any fully-connected tree to perform a horizontal shuffle with permute accumulate circuits, and includes vector flip-flops, stacked min-delay buffers, shared gates to average min-sized transistor variation, and ultra-low-voltage split-output (ULVS) level shifters improving logic V MIN by 150mV, while enabling peak energy efficiency of 585GOPS/W measured at 260mV, 50°C. The permutation engine occupies a dense layout of 0.048mm 2 (Fig. 10.1.7) while achieving: (i) nominal register file performance of 1.8GHz, 106mW measured at 0.9V, 50°C; (ii) robust register file functionality measured down to 280mV (subthreshold) with peak energy efficiency of 154GOPS/W; (iii) scalable permute crossbar performance of 2.9GHz, 69mW measured at 1.1V, 50°C with deep sub-threshold operation at 240mV, 10MHz consuming 19μW; and (iv) a 64b 4×4 matrix transpose algorithm with 53% energy savings and 42% improved peak throughput of 263Gbps measured at 1.8GHz, 0.9V.